2019
DOI: 10.3892/mmr.2019.10511
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of the contribution of mRNAs and long non‑coding RNAs to the pathogenesis of asthma

Abstract: asthma, a common but poorly controlled disease, is one of the most serious health problems worldwide; however, the mechanisms underlying the development of asthma remain unknown. long non-coding rnas (lncrnas) and mrnas serve important roles in the initiation and progression of various diseases. The present study aimed to investigate the role of differentially expressed lncrnas and mrnas associated with asthma. differentially expressed lncrnas and mrnas were screened between the expression data of 62 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Disturbance of amino sugar and nucleotide sugar metabolism was found in hypertrophic cardiomyopathy 47 and asthma, a chronic inflammatory airway disease with the characteristic of airway remodeling. 48 N -acetyl- d -glucosamine 6-phosphate, an intermediate metabolite of amino sugar and nucleotide sugar metabolism, which was dysregulated both in PAs and the RV in our PAH model, was identified as a potential biomarker for the diagnosis of coronary heart disease (a kind of cardiovascular disease that was thought to undergo a metabolic shift). 49 Taken together, our results suggested that the perturbation of energy metabolism was involved in the development of flow-associated PAH, especially the carbohydrate metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance of amino sugar and nucleotide sugar metabolism was found in hypertrophic cardiomyopathy 47 and asthma, a chronic inflammatory airway disease with the characteristic of airway remodeling. 48 N -acetyl- d -glucosamine 6-phosphate, an intermediate metabolite of amino sugar and nucleotide sugar metabolism, which was dysregulated both in PAs and the RV in our PAH model, was identified as a potential biomarker for the diagnosis of coronary heart disease (a kind of cardiovascular disease that was thought to undergo a metabolic shift). 49 Taken together, our results suggested that the perturbation of energy metabolism was involved in the development of flow-associated PAH, especially the carbohydrate metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Dolcino et al [ 13 ] analyzed the transcript profiles of rheumatoid arthritis (RA) patients and healthy donors and found that lncRNA RP11-4989.15 plays an important role in RA pathogenesis. Another study screened eight important lncRNAs interacting with 52 differentially expressed genes enriched in asthma-associated pathways, and these lncRNAs have the potential to serve as underlying biomarkers useful for the future development of therapeutic strategies [ 14 ]. Nevertheless, specific biomarkers for childhood asthma have not been identified, and the roles of lncRNAs in childhood asthma remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A bioinformatics study using gene ontology and KEGG enrichment analysis of genes shows that, in asthmatic patients, the level of ZNF667-AS1 is downregulated when compared to healthy controls. This suggests that it may play a role in the pathogenesis of asthma [23]. ZNF667-AS1 was found to be upregulated in the plasma of patients with myocardial infarction when compared with healthy controls.…”
Section: The Functional Role Of Lncrna Mort (Znf667-as1) In Human Diseasesmentioning
confidence: 93%